9.7k views
5 votes
Select the correct answer. Consider the explicit formula of two sequences. (n) = 2n + 3 g() = 3( - 1) - Which mathematical statement is correct? g(1) > f(1) g(3) = f(3) f(1) < g(2) f(10) = g(4)

Select the correct answer. Consider the explicit formula of two sequences. (n) = 2n-example-1

1 Answer

4 votes

The function g is given by:


\begin{gathered} g(n)=3^((n-1)) \\ \text{ Substitute }n=3\text{ into the equation:} \\ g(3)=3^((3-1))=3^2=9 \end{gathered}

The function f is given by:


\begin{gathered} f(n)=2n+3 \\ \text{ Substitute }n=3\text{ into the equation:} \\ f(3)=2(3)+3=9 \end{gathered}

Therefore,

g(3) = f(3)

User Zaki Aziz
by
5.5k points